Life After Being a Pathology Department Chair - David N. Bailey MD; Mary F. Lipscomb MD; Fred Gorstein MD; David Wilkinson MD, PhD; Fred Sanfilippo MD, PhD (Elsevier, 2016)
Although there is a considerable literature on transition of faculty members to the position of department chair, there is a dearth of publications about transitioning from the chair to other activities including retirement. The Association of Pathology Chairs senior fellows (all of whom are former chairs of academic departments of pathology) made this topic a focus of discussion at the Association of Pathology Chairs 2016 Annual Meeting. Of the 33 senior fellows engaged in this discussion, following their time as chairs, a small majority (18) transitioned to other administrative posts within or outside the university, while the others either returned to the active faculty (7) or retired (8). The motivating factors and influences for transitioning from the chair were probed along with the processes used in executing the transition, such as the development of transition plans. The reasons for selecting the specific type of postchair activity were also investigated. There was extraordinary diversity in the type of post-chair activities pursued. To our knowledge, no other medical specialty has examined these issues, which may be potentially relevant for the career planning of active chairs.